Axial parkinsonian symptoms can be improved: the role of levodopa and bilateral subthalamic stimulation. Issue 5 (1st May 2000) - Bejjani, Boulos-Paul; Gervais, David; Arnulf, Isabelle; Papadopoulos, Savas; Demeret, Sophie; Bonnet, Anne-Marie; Cornu, Philippe; Damier, Philippe; Agid, Yves
Abstract : OBJECTIVE: To assess the effects of high frequency stimulation of the subthalamic nucleus (STN) on axial symptoms occurring in advanced stages of Parkinson's disease (PD). METHODS: The efficacy of STN stimulation on total motor disability score (unified Parkinson's disease rating scale (UPDRS) part III) were evaluated in 10 patients with severe Parkinson's disease. The subscores were then studied separately for limb akinesia, rigidity, and tremor, which are known to respond to levodopa, and axial signs, including speech, neck rigidity, rising from a chair, posture, gait, and postural stability, which are known to respond less well to levodopa. Patients were clinically assessed in the "off" and "on" drug condition during a levodopa challenge test performed before surgical implantation of stimulation electrodes and repeated 6 months after surgery under continuous STN stimulation. A complementary score for axial symptoms from the "activities of daily living" (ADL)—that is, speech, swallowing, turning in bed, falling, walking, and freezing—was obtained from each patient's questionnaire (UPDRS, part II). RESULTS: Improvements in total motor disability score (62%), limb signs (62%), and axial signs (72%) obtained with STN stimulation were statistically comparable with those obtained with levodopa during the preoperative challenge (68%, 69%, and 59%, respectively). When levodopa and STN stimulation were combined there was a further improvement in total motor disability (80%) compared with preoperative levodopa administration. This consisted largely of an additional improvement in axial signs (84%) mainly for posture and postural stability, no further improvement in levodopa responsive signs being found. Axial symptoms from the ADL showed similar additional improvement when levodopa and STN stimulation were combined. CONCLUSION: These findings suggest that bilateral STN stimulation improves most axial features of Parkinson's disease and that a synergistic effect can be obtained when stimulation is used in conjunction with levodopa treatment.